ISLAMISASI DI CIREBON: PERAN DAN PENGARUH WALANGSUNGSANG PERSEPEKTIF NASKAH CARIOS WALANGSUNGSANG - Siti Zulfah (IAIN Syekh Nurjati Cirebon, 2018)
AbstractIslamization is a theme that continues to this day. Islamization can be defined as Islamic, through the conversion process of Religion. Cirebon Islamic Society is the result of mixing between indigenous (ethnic Javanese-Sunda) with immigrants (traders-Sufis) who are Muslims. Walangsungsang plays an active role in the opening, the spread of civilization (culture), the founder of the center of Islamic government. Keraton Pakungwati as the legitimacy of central Islamic government in Cirebon. This paper seeks to identify a biography of Walangsungsang (fact or myth) and to understand how Walangsungsang's role and influence in the Islamization of Cirebon is the perspective of the Carios Walangsungsang manuscript. This research is done by searching the manuscript of Cariyos Walangsungsang, references both books and research results about the history of Islam in Cirebon, and placing some historical places in Cirebon such as Keraton, petilasan (Tomb of Mbah Kuwu Cirebon Girang) Walangsungsang. Historical Approach to tracing historical facts, then explored in chronological order. This paper produces historical facts that the role of Walangsungsang as the first spreader of Islam in Cirebon from the Hindu-Buddhist kingdom (Padjajaran), cultivate Cirebon land, and founder of Pakungwati Islamic Kingdom. For his role Walangsungsang influential and changing Religion and culture of Islamic society Cirebon become more characteristic with the pattern of arranging a diverse society and a complex social hierarchy.Keywords: islamization, Walangsungsang, Cirebon